Effective Approaches of Improving the Performance of Chalcogenide Solid Electrolytes for All-Solid-State Sodium-Ion Batteries - Dai, Hanqing; Xu, Wenqian; Hu, Zhe; Chen, Yuanyuan; Wei, Xian; Yang, Bobo; Chen, Zhihao; Gu, Jing; Yang, Dan; Xie, Fengxian; Zhang, Wanlu; Guo, Ruiqian; et al. (Frontiers in Energy Research, 2020)
All solid-state sodium-ion batteries (SIBs) possess the advantages of rich resources, low price and high security, which is one of the best alternatives for large-scale energy storage systems in the future. Also, the chalcogenide solid electrolytes (CSEs) of SIBs have the characteristics of excellent room-temperature ionic conductivity (10-3 10-2 S cm-1), low activation energy (＜0.6 eV), and easy cold-pressing consolidation, etc. Hence, CSEs have become a very active area of all solid-state SIBs in recent years. In this review, the modification methods and implementation technologies of CSEs are summarized, and the structure and electrochemical performance of the CSEs are discussed. Furthermore, the auxiliary function of first-principle calculations for modification is introduced. Ultimately, we describe the challenges of the CSEs and propose some strategic suggestions.